PERBEDAAN TINGKAT KECEMASAN WANITA BEKERJA DAN TIDAK BEKERJA DALAM MENGHADAPI MENOPAUSE DI KELURAHAN DONAN KABUPATEN CILACAP - Ayu L, Sherly; -, Hartati; Tri Y, Danang (Jurnal Ilmiah Kesehatan Keperawatan, 2014)
Menopause is known as the cessation of menstrual periods due to the degeneration function of ovaries to produce estrogen and progesterone hormones. The changing of both hormones will affect the physical and psychological change which will increase women’s anxiety. Employed women doesn’t easily experience anxiety since they have things to do that can distract the complaints felt during pre-menopause. Thus, the anxiety level of employed women is relatively lower than that of unemployed women. This is a quantitative descriptive research with comparative method which is aimed at determining whether or not there are differences in anxiety level of employed women and unemployed women facing menopause. The researcher used cluster sampling to take the samples. The samples of the research were 60 respondents. Analysis of data in this research used the Mann Whitney (U) test. The result shows the difference between anxiety facing menopause in employed women with anxiety facing menopause in unemployed women i.e p value = 0.000 < α = 0.05. The writer expects that this research can give implications in the area of public health and that women who do not work can better prepare themselves to face menopause. Keywords : anxiety level, employed women and unemployed women, menopause